ECONOMIC ANALYSIS OF INIMICAL RELIGIOUS ACTIVITIES IN NIGERIA - Anizoba, Emmanuel C; Akabike, Gladys (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2021)
The impact of the activities of different types of religion such as Christianity, Islam and African Traditional Religion in Nigeria is enormous and should not be over looked. The study aimed at exploring some of the effects of the activities of aforementioned different types of religion in the Nigerian Economy. The study adopts a qualitative phenomenological research design and descriptive method for data analysis. Personal interview forms a primary source of data collection while the secondary source includes library resources. The study reveals that, Government neglects, oppression, domination, exploitation, victimization, discrimination, marginalization, nepotism and bigotry are some of the causes of religious violence in Nigeria. The study also identified poverty, corruption, non-implementation of previous probe panel reports, impunity of past perpetrators of the violence, proliferation of preachers and worship centres, provocative and inciting utterances, sensational journalism, political manipulation of religion, incitement in the social media and mobile telephone among others as key causes of religious violence in northern Nigeria. The study also notes that, the effects of these inimical activates of these religions are enormous in the Nigerian economy, where in addition to the gratuities killing and maiming of thousands of persons, properties worth billions of naira have been destroyed. Certainly, these huge losses have deprived the nation of needed manpower and services for the growth of its wobbling economy. The study recommends among other things that Nigeria should consider her diverse cultures as a blessing and live in peace with each other irrespective of religious denomination to ensure peaceful and a healthy nation, since a healthy nation is a wealthy nation.